Modalities of the First Female Regional Head in North Maluku in the 2020 Sula Islands Regional Election - Syamsul Bahri Abd. Rasyid; Dian Eka Rahmawati; Misran; Herdin Arie Saputra (Politicon : Jurnal Ilmu Politik, 2025)
This study aims to examine the modalities of Fifian Adeningsi Mus as a candidate in the 2020 Sula Islands regional election. Using qualitative methods and a case study approach, this study employed content analysis techniques on 174 news items from seven local media outlets that reported most intensively on Fifian’s participation in the Sula Islands regional election during the reporting period from August 28, 2020, to February 28, 2021. The results, based on NVivo 12 plus analysis, indicate that social modality is the most dominant modality narrated by local media in North Maluku, compared to economic, political, cultural, and symbolic modalities. This article contributes to explaining the election of women as regional heads (especially for regions that have never had female regional heads before), supported by the accumulation of previously built modalities. However, the main contribution to women’s election comes from dynastic politics. Therefore, the presence of women in strategic positions can be encouraged through a competitive selection process and a focus on the capacity and capabilities of candidates, so that the election of women as regional heads does not rely solely on the family name (political dynasty).